Augmented Reality Navigation Combined with Fluorescence Imaging for Colorectal Liver Metastases - RUKH, GUL; ALI, MARVA; MALIK, ALEENA AMIR; SHAHID, ABDUL REHMAN; SHAHID, ABDULLAH; ATIF, MUHAMMAD (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Parenchyma-sparing hepatectomy (PSH) is becoming more popular as an option in the treatment of colorectal liver metastases (CRLM). The use of augmented reality navigation (ARN) and indocyanine green fluorescence imaging (FI) has the potential to enhance the accuracy of surgery. Objective: To compare the perioperative and oncologic outcome of ARN-FI-aided laparoscopic PSH and standard laparoscopic PSH using a synthetic IPTW-modeled cohort (N = 300). Methods: Artificial cohort of 300 patients (150 ARN-FI, 150 Nonarn-FI), simulated based on published distributions and balanced based on IPTW considerations. Outcomes: EBL, operative time, big-time resection, big-time morbidity, LOS, RFS, OS. Results: ARN-FI was linked to much less EBL (180 85 mL vs 350 140 mL: p < 0.001), higher R0 rate (94.7% vs 88.0; p = 0.019), shorter operating time (210 45 min vs 175 38 min: p < 0.001), shorter LOS (5.5 1.8 d vs 7.2 2.5 d: p < 0.0 Downward trend of significant morbidity (6.0% vs 11.3%; p = 0.07). Conclusions: ARN-FI enhances the intraoperative accuracy, lessens blood loss, and amplifies margin negative resections, providing improved RFS with augmented operating time. Potential validation advised.